Two new species of Australian Eutarsopolipus (Acariformes: Podapolipidae) from Nurus medius (Coleoptera: Carabidae) - Seeman, Owen D. (Zootaxa, 2019)
Eutarsopolipus burwelli sp. nov. and E. echinatus sp. nov. (Acari: Podapolipidae) are described from Nurus medius Darlington, 1961 (Coleoptera: Carabidae), a large burrowing carabid beetle found in the rainforests of coastal central Queensland, Australia. Eutarsopolipus burwelli belongs to the ochoai species group, which is herein refined, and E. echinatus is placed tentatively in the pterostichi species group. A revised key to the species groups of Eutarsopolipus is provided. The synhospitalic species of Eutarsopolipus are reviewed and synhospitality within the genus is discussed.